Simulation of stirred yoghurt processing in plate heat exchangers - Fernandes, Carla S. (2005)
In the present work, simulations of stirred yoghurt processing in a plate heat exchanger were performed using computational fluid dynamics (CFD) calculations and the results compared with experimental data, showing a very good agreement. A Herschel–Bulkley model for the viscosity and an Arrhenius-type term for the temperature dependence were used to model the thermo-rheological behaviour of yoghurt. The heat exchanger used in this study operates in a parallel arrangement, thus simplifying the problem to the construction of a single complete 3D channel. After analysis of the velocity field and fanning friction factors, laminar flow was observed for all the operating conditions used and relations are proposed for the present heat exchanger between fanning factors and Reynolds number and between mean shear rate and mean velocity of yoghurt.